2006
DOI: 10.2172/876527
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of satellite remote sensing for identifying uranium mines and mills.

Abstract: In this report, we systematically evaluate the ability of current-generation, satellite-based spectroscopic sensors to distinguish uranium mines and mills from other mineral mining and milling operations. We perform this systematic evaluation by (1) outlining the remote, spectroscopic signal generation process, (2) documenting the capabilities of current commercial satellite systems, (3) systematically comparing the uranium mining and milling process to other mineral mining and milling operations, and (4) iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, those studies were not specifically targeting active mines and/or waste piles. After reviewing the criteria for using spaceborne multispectral and hyperspectral imagery for identifying uranium mines and mills, Stork et al [12] concluded that uranyl-bearing minerals tend to occur in concentrations too low to be detected. They also noted that spectrally more abundant gangue minerals would have to be used instead.…”
Section: Endmembermentioning
confidence: 99%
“…However, those studies were not specifically targeting active mines and/or waste piles. After reviewing the criteria for using spaceborne multispectral and hyperspectral imagery for identifying uranium mines and mills, Stork et al [12] concluded that uranyl-bearing minerals tend to occur in concentrations too low to be detected. They also noted that spectrally more abundant gangue minerals would have to be used instead.…”
Section: Endmembermentioning
confidence: 99%